SWOT Analysis and Ansoff Matrix in Creative Food Industry Business Development: A Study on Creative Food Business “Komala” - Suciati, Tri Ratna; Dodi Kurniawan; M. Dery Iswahyudin (HM Publisher, 2020)
The number of entrepreneurs in the food and beverage industry is spread throughout Indonesia. Komala is a business engaged in the culinary or food and beverage industry headquartered in the city of Tangerang. Komala has a local food concept that is packaged in a modern and practical way. This research is qualitative research by conducting interviews with several resource persons who run competent and sustainable food and beverages business. In this study, interviews were conducted with representatives from several restaurant, namely, GB, DBJ, H, KC, SKS, and RR as benchmarks in the Komala food business. The author prepares a list of questions regarding the information needed to approach the SWOT analysis and Ansoff Matrix to the informants. Based on results, it can be concluded that the strategies that Komala's business must implement to develop are strengths (having a structured SOP and competitive prices), weakness (limited human resources and the absence of a physical store), opportunities (starting to collaborate with online food delivery modes), threats (anticipating the increase in raw materials and making new innovative products)